The expression profile of exosomal miRNAs in cervical cancer cells (HeLa) compared to normal cells and evaluating the key genes related to them - Marzieh Naderi Boldaji; Kambiz Ahmadi; Somayeh Reiisi (Mashhad University of Medical Sciences, 2023)
Introduction: Cervical cancer is the fourth most common cancer among women worldwide and is a heterogeneous disease. The exosomal miRNAs could be applied as diagnostic biomarkers and therapeutic targets in cervical cancer. The present study was performed with aim to use a bioinformatics analysis to identify key miRNAs and related genes and pathways in exosomes derived from cervical cancer cells. Methods: In this study, the differential expression of exosomal miRNA and RNAs in healthy and HeLa cells was investigated by analyzing the GEO database for miR-seq and RNA-seq in R software. Subsequently, overlapped miRNA target genes and differentially mRNA from exosome were selected and then, GO and KEGG pathway analysis was performed. The overlapped genes were integrated to construct a PPI network and hub genes selection. Results: In the present study, it was observed that 31 miRNAs were upregulated and 16 miRNAs were downregulated in exosomes. Also, 341 overlapped genes from miRNAs targets and mRNA-seq were selected for future analysis. GO analysis indicated that overlapped genes were significantly enriched in the leucine transport, MAP kinase phosphatase activity, and glutamine transport. KEGG analysis suggested that the genes were enriched in cellular senescence, p53 signaling pathway and cell cycle. The top ten genes including CCNB1, BUB1, KIF20A, MKI67, FOXM1, BIRC5, NCAPH, ZWINT, GINS2, and ASF1B were identified from the PPI network. Conclusion: The results identified key miRNAs with altered expression and characterizing key genes in exosomes derived cervical cancer cells. This study will provide novel insights to determine the potential mechanisms associated exosomes derived from cancer cells in cervical cancer progression.